2008
DOI: 10.1002/hbm.20690
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of low‐frequency repetitive transcranial magnetic stimulation during movement in healthy subjects and acute stroke patients. A PET study

Abstract: The aim of the study was to investigate, with an rTMS/PET protocol, the after-effects induced by 1-Hz repetitive transcranial magnetic stimulation (rTMS) in the regional cerebral blood flow (rCBF) of the primary motor cortex (M1) contralateral to that stimulated during a movement. Eighteen healthy subjects underwent a baseline PET scan followed, in randomized order, by a session of Real/Sham low-frequency (1 Hz) subthreshold rTMS over the right M1 for 23 min. The site of stimulation was fMRI-guided. After each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 67 publications
3
26
0
2
Order By: Relevance
“…Cerebral perfusion in the sensory-motor ROIs at rest did not change with iTBS confirming previous observations in rTMS/PET studies at rest [Conchou et al, 2008]. This indicates that the BOLD signal decrease is not caused by a global change in brain perfusion within the network and supports the idea that the facilitating effect of iTBS is activity-dependent.…”
Section: Functional Imaging At Restsupporting
confidence: 88%
“…Cerebral perfusion in the sensory-motor ROIs at rest did not change with iTBS confirming previous observations in rTMS/PET studies at rest [Conchou et al, 2008]. This indicates that the BOLD signal decrease is not caused by a global change in brain perfusion within the network and supports the idea that the facilitating effect of iTBS is activity-dependent.…”
Section: Functional Imaging At Restsupporting
confidence: 88%
“…This pattern was common at all patients in PVS, independently of their etiology ( p FWE corrected Ͻ0.05). Finally, a psychophysiological interaction 1,[16][17][18][19][20] analysis of the activity signal of the left S1M1 cortex (proprioceptive stimulus Ϫ rest) enabled us to demonstrate a loss of functional connectivity between this primary area (left S1M1) and the high-level associative structures recruited by the task (right and left BA 40) in patients, whereas functional connectivity was found in the controls (corrected p value Ͻ0.05; figure 4). Nevertheless, the functional link between these primary and secondary areas was different between the ipsilateral and contralateral sides in patients in PVS (figure 4).…”
Section: Resultsmentioning
confidence: 93%
“…[11][12][13] Then, we performed a functional connectivity analysis. 1,[16][17][18][19][20] The ARAS, whose activity was functionally correlated to that of the precuneus in healthy subjects, showed no correlation with this structure in the patient group (corrected p value Ͻ0.05; figure 2). Comparison of deactivations between the 2 groups showed a significantly smaller degree of deactivation in the precuneus in the patient group than in the control group (SVC of a 12-mmradius sphere applied on precuneus, p FWE corrected Ͻ0.05; figure 3).…”
Section: Resultsmentioning
confidence: 98%
“…M1 is involved in both the generation and learning of movement and blood flow during hand movement scales with basic task demands, e.g., tapping frequency (Sadato et al, 1996) and grip force (Sehm, Perez, Xu, Hidler, & Cohen, 2010). One study, (Conchou et al, 2009) found changes in movement-related blood flow in contralateral M1 and connected areas, after inhibitory (1 Hz) rTMS in a comparison to rest. Our paradigm did not contain a resting condition and the motoric demands of the task were constant across conditions.…”
Section: 4 Discussionmentioning
confidence: 99%